Relationship between QT and JT peak interval variability in prepubertal children. Issue 4 (17th February 2017) - Takeuchi, Yuka; Omeki, Yumi; Horio, Kayo; Nishio, Miki; Nagata, Rina; Oikawa, Shota; Mizutani, Yuri; Nagatani, Arisa; Funamoto, Yuri; Uchida, Hidetoshi; Fujino, Masayuki; Eryu, Yoshihiko; et al.
Abstract : Background: The QT variability index (QTVI) is a noninvasive index of repolarization lability that has been applied to subjects with cardiovascular disease. QTVI provides a ratio of normalized QT variability to normalized heart rate variability, and therefore includes an assessment of autonomic nervous activity. However, measurement of QT time is particularly difficult in children, who exhibit physiologically high heart rates compared with adults. In this study, we developed a set of standard values of J‐point to Tpeak interval (JTp) for infants by age, and assessed the correlation of QTVI with the JTp variability index (JTpVI). Methods: Subjects included 623 infants and children (0–7 years of age) without heart disease and 57 healthy university students. All subjects were divided into three groups by age. QTVI and JTpVI were calculated based on an electrocardiogram, and age‐specific standard values, a gender‐specific classification, and a standard growth curve were constructed. Results: JTpVI markedly decreased in infancy and slowly decreased thereafter, reaching adult values by school age. There was also a strong correlation of JTpVI with QTVI ( r  = .856). Conclusions: JTp can be used to evaluate the variability of the repolarization time in healthy infants, and may be useful for detection of early repolarization abnormalities.